2006
DOI: 10.1007/s00417-006-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral retinitis pigmentosa with amblyopia in the fellow eye

Abstract: Unilateral retinitis pigmentosa with amblyopia in the other eye is a rare condition. The patient presented here had a case of unilateral retinitis pigmentosa with the other eye with ametropic amblyopia. It is necessary to perform functional and morphological ophthalmological examinations to confirm the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…There was difficulty in establishing an aetiology in many patients but, importantly, a family history suggesting a heritable cause was present in only two of the patients. The observation that a genetic diagnosis could be reached in only two cases is consistent with previous studies of atypical that have suggested a high incidence of acquired disease (Joseph 1951;Spadea et al 1998;Chen et al 2006). Detailed electrophysiological testing showed generalized retinal dysfunction in the eye with pigmentary changes that varied in severity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…There was difficulty in establishing an aetiology in many patients but, importantly, a family history suggesting a heritable cause was present in only two of the patients. The observation that a genetic diagnosis could be reached in only two cases is consistent with previous studies of atypical that have suggested a high incidence of acquired disease (Joseph 1951;Spadea et al 1998;Chen et al 2006). Detailed electrophysiological testing showed generalized retinal dysfunction in the eye with pigmentary changes that varied in severity.…”
Section: Discussionsupporting
confidence: 90%
“…; Chen et al. ). Detailed electrophysiological testing showed generalized retinal dysfunction in the eye with pigmentary changes that varied in severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unilateral retinitis pigmentosa is a rare degeneration of the photoreceptors involving retinitis pigmentosa‐like changes in one eye with the other eye completely unaffected. The criteria 6 for diagnosis of unilateral retinitis pigmentosa are:…”
Section: Discussionmentioning
confidence: 99%